2017
DOI: 10.20944/preprints201703.0052.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oral Mucositis: Melatonin Gel an Effective New Treatment

Abstract: Abstract:The current treatment for cervico-facial cancer involves radio and/or chemotherapy.Unfortunately, cancer therapies can lead to local and systemic complications such as mucositis, which is the most common dose-dependent complication in the oral cavity and gastrointestinal tract.Mucositis can cause a considerably reduced quality of life in cancer patients already suffering from physical and psychological exhaustion. However, melatonin, whose role in the treatment of mucositis has recently been investiga… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Melatonin reportedly protects various organs from chemotherapy‐ and radiotherapy‐induced toxicity . Thus, the combination of melatonin with rapamycin may both achieve an enhanced oncostatic effect and overcome a major limitation of anticancer treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin reportedly protects various organs from chemotherapy‐ and radiotherapy‐induced toxicity . Thus, the combination of melatonin with rapamycin may both achieve an enhanced oncostatic effect and overcome a major limitation of anticancer treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Melatonin (N‐acetyl‐5‐methoxytryptamine) is a potent free radical scavenger with anti‐oxidant and anti‐inflammatory properties, which has well‐known functions in immune system regulation, modulation of mitochondrial activity, and regulation of cell death and autophagy . Moreover, melatonin has attracted attention as a natural oncostatic agent that can suppress neoplastic growth in a variety of tumours .…”
Section: Introductionmentioning
confidence: 99%
“…This assumption has recently been questioned, since several organs and glands were claimed to produce melatonin (Hevia et al, ; Venegas et al, ; Acuña‐Castroviejo et al, ) and mitochondria are believed to be the preferentially sites of melatonin production in peripheral tissues (Tan D‐X et al, , Reiter et al, ; Suofu et al, ). Moreover, the oral mucosa and the salivary glands themselves have been considered extrapineal sources of this indoleamine, because the enzymes involved in melatonin synthesis were found in both the oral mucosa and the glandular parenchyma (Shimozuma et al, ; Abdel Moneim et al, ). Moreover, besides passive diffusion, new evidence supports the existence of an as yet not fully defined mechanism that may regulate the diffusion and storage of melatonin inside the cells (Venegas et al, ; Hevia et al, ).…”
mentioning
confidence: 99%
“…Many studies in the literature reported the use of melatonin in the treatment of different human oral conditions due to its oncostatic and cytoprotective properties (Mihandoost, Shirazi, Mahdavi, & Aliasgharzadeh, ; Wang et al, ). Both animals (Abdel Moneim et al, ; Meltz, Reiter, Herman, & Kumar, ) and human (Reiter, Herman, & Meltz, ; ) studies have shown melatonin to be protective against radiation‐induced cellular damage. In 2017, Abdel Moneim et al () demonstrated that melatonin gel shields rats from postradiation oral mucositis.…”
Section: Introductionmentioning
confidence: 99%
“…Both animals (Abdel Moneim et al, ; Meltz, Reiter, Herman, & Kumar, ) and human (Reiter, Herman, & Meltz, ; ) studies have shown melatonin to be protective against radiation‐induced cellular damage. In 2017, Abdel Moneim et al () demonstrated that melatonin gel shields rats from postradiation oral mucositis.…”
Section: Introductionmentioning
confidence: 99%